Association of lymphocyte-to-monocyte ratio with the no-reflow phenomenon in patients who underwent a primary percutaneous coronary intervention for ST-elevation myocardial infarction. Issue 8 (December 2015) - Kurtul, Alparslan; Yarlioglues, Mikail; Celik, Ibrahim Etem; Duran, Mustafa; Elcik, Deniz; Kilic, Alparslan; Oksuz, Fatih; Murat, Sani Namik
Abstract : Background: Recently, it has been shown that the lymphocyte-to-monocyte ratio (LMR) is a novel inflammatory marker. A decreased LMR is associated significantly with a high risk for vascular endpoints in patients with peripheral arterial disease. We aimed to investigate whether LMR on admission is associated with no-reflow after a primary percutaneous coronary intervention (PCI) in patients with ST-elevation myocardial infarction (STEMI). Patients and methods: A total of 857 patients (mean age 58.9±13.1 years, 75.6% men), who were admitted to our hospital for STEMI and undergoing primary PCI within 12 h of onset of symptoms, were recruited. LMR was calculated by dividing the lymphocyte count by the monocyte count. The patients were divided into two groups according to the postprocedural thrombolysis in myocardial infarction (TIMI) flows: no-reflow and normal-reflow. No-reflow was defined as a final TIMI flow of 2 or less or final TIMI flow of 3 with a myocardial blush grade of less than 2. Results: Admission LMR levels were significantly lower in patients with no-reflow than in patients with normal-reflow (1.85±1.01 vs. 3.64±1.74, P <0.001). A receiver-operating characteristic analysis indicated that an LMR value of less than 2.292 and had a 76.3% sensitivity and a 72.5% specificity in predicting no-reflow. Multivariate analysis showed that LMR less than 2.292 [odds ratio (OR) 2.657, P =0.030], Killip class at least 2 at admission (OR 3.442, P =0.039), baseline infarct artery patency (OR 0.260, P =0.004), neutrophil count (OR 1.213, P =0.002), and total stent length (OR 1.059, P =0.001) were independent factors for predicting no-reflow. Conclusion: Our results suggested that LMR could be a simple and useful marker to predict high risk of patients for no-reflow in patients with STEMI who underwent primary PCI.